2010
DOI: 10.1080/13676261003801754
|View full text |Cite
|
Sign up to set email alerts
|

Transition into first sex among adolescents in slum and non-slum communities in Nairobi, Kenya

Abstract: While early sexual experiences are a key marker of the transition from childhood to adulthood, it is widely acknowledged that precocious initiation of sexual activity predisposes adolescents to negative health and psychological outcomes. Extant studies investigating adolescent sexuality in sub-Saharan Africa often rely on cross-sectional data lacking information on the socialpsychological underpinnings of adolescent behavior. Through the theoretical lens of the protection-risk conceptual framework, this paper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
93
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(103 citation statements)
references
References 30 publications
9
93
1
Order By: Relevance
“…This counterintuitive relationship has also been observed in Nairobi, especially on the risk of unwanted pregnancies among young women (Beguy, Mumah, & Gottschalk, 2014). This finding was in line with another study (Kabiru, Beguy, Undie, Zulu, & Ezeh, 2010), which found that a high level of parental supervision was positively associated with a high risk of sexual debut among adolescent girls, which in turn was also associated with the risk of unwanted pregnancies. Excessive parental control, as perceived by adolescent girls, may increase risky sexual behaviors (Rodgers, 1999).…”
Section: Discussionsupporting
confidence: 90%
“…This counterintuitive relationship has also been observed in Nairobi, especially on the risk of unwanted pregnancies among young women (Beguy, Mumah, & Gottschalk, 2014). This finding was in line with another study (Kabiru, Beguy, Undie, Zulu, & Ezeh, 2010), which found that a high level of parental supervision was positively associated with a high risk of sexual debut among adolescent girls, which in turn was also associated with the risk of unwanted pregnancies. Excessive parental control, as perceived by adolescent girls, may increase risky sexual behaviors (Rodgers, 1999).…”
Section: Discussionsupporting
confidence: 90%
“…This study confirms the independently protective effects of caregiver supervision and support, especially as related to transactional sex and sexual violence [32,37]. Similarly, being in school is strongly associated in this study with reduced sexual risks that include being sexually active.…”
Section: Discussionsupporting
confidence: 87%
“…Therefore, it is likely that changing family structure, caregiver relationships, and living arrangements impact orphaned adolescents’ sexual risk practices. Changes in caregiver and care environment upon the death or disappearance of one or both parents may expose orphaned and separated adolescents to sexual exploitation [22] and diminish or eliminate protective mechanisms, normally enacted by parents, that reduce adolescent risky behaviours [3032]. …”
mentioning
confidence: 99%
“…Kenya DHS findings also indicate that the gap between wanted and observed fertility is greatest among poor women such as those living in urban informal settlements. Evidence has shown that Nairobi informal settlement residents exhibit significant disadvantages with respect to living conditions, morbidity (African Population and Health Research Center 2002;Taffa, Chepngeno, and Amuyunzu-Nyamongo 2005), access to health services, including family planning services, (Essendi, Mills, and Fotso 2011;Fotso et al 2009;Fotso, Ezeh, and Oronje 2008;Ziraba et al 2009), mortality (Ziraba, Kyobutungi, and Zulu 2011;Kyobutungi et al 2008), sexual violence and risky sexual practices (Beguy et al 2009;Kabiru et al 2010;Zulu, Dodoo, and Ezeh 2002) relative to other population sub-groups, including rural residents. Living in such an environment may limit women's ability to control their fertility and implement their fertility preferences.…”
Section: Introductionmentioning
confidence: 98%